2019
DOI: 10.7554/elife.44258
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of random X-inactivation to imprinted X-inactivation by maternal PRC2

Abstract: Imprinted X-inactivation silences genes exclusively on the paternally-inherited X-chromosome and is a paradigm of transgenerational epigenetic inheritance in mammals. Here, we test the role of maternal vs. zygotic Polycomb repressive complex 2 (PRC2) protein EED in orchestrating imprinted X-inactivation in mouse embryos. In maternal-null (Eedm-/-) but not zygotic-null (Eed-/-) early embryos, the maternal X-chromosome ectopically induced Xist and underwent inactivation. Eedm-/- females subsequently stochastical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 72 publications
(124 reference statements)
6
74
0
Order By: Relevance
“…During their brief presence in pre-implantation embryos, some of the H3K27me3 domains can function as an imprinting mechanism to regulate allelic expression ( Inoue et al., 2017 , 2018 ). For example, an H3K27me3 domain represses the maternal copy of Xist , a master regulator of X chromosome inactivation (XCI) ( Loda and Heard, 2019 ), leading to paternal XCI in mouse early embryo ( Harris et al., 2019 ; Inoue et al., 2018 ). Loss of maternal Embryonic Ectoderm Development (EED), a component of PRC2, results in defects of paternal XCI and male-biased lethality ( Harris et al., 2019 ; Inoue et al., 2018 ).…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…During their brief presence in pre-implantation embryos, some of the H3K27me3 domains can function as an imprinting mechanism to regulate allelic expression ( Inoue et al., 2017 , 2018 ). For example, an H3K27me3 domain represses the maternal copy of Xist , a master regulator of X chromosome inactivation (XCI) ( Loda and Heard, 2019 ), leading to paternal XCI in mouse early embryo ( Harris et al., 2019 ; Inoue et al., 2018 ). Loss of maternal Embryonic Ectoderm Development (EED), a component of PRC2, results in defects of paternal XCI and male-biased lethality ( Harris et al., 2019 ; Inoue et al., 2018 ).…”
Section: Main Textmentioning
confidence: 99%
“…For example, an H3K27me3 domain represses the maternal copy of Xist , a master regulator of X chromosome inactivation (XCI) ( Loda and Heard, 2019 ), leading to paternal XCI in mouse early embryo ( Harris et al., 2019 ; Inoue et al., 2018 ). Loss of maternal Embryonic Ectoderm Development (EED), a component of PRC2, results in defects of paternal XCI and male-biased lethality ( Harris et al., 2019 ; Inoue et al., 2018 ). Such imprinting is lost in embryonic lineages after implantation but is maintained in extraembryonic tissues by DNA methylation instead, which is considered as a more stable epigenetic mark ( Chen et al., 2019b ).…”
Section: Main Textmentioning
confidence: 99%
“…We recently demonstrated that oocyte-specific H3K27me3 serves as the primary imprinting mark to repress the maternal transcription of several dozens of PEGs in early embryos, including all imprinted genes that were previously known to be independent of oocyte DNA methylation (9,10). Maternal H3K27me3 also regulates im-printed X inactivation by repressing the maternal transcription of Xist in preimplantation embryos (10)(11)(12). Notably, maternal allelebiased H3K27me3 correlates with paternal-specific gene expression in human morulae (13).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Inoue et al [28] and Harris et al [29] recently showed that in mice, the choice of active X is determined prenatally. Having been imprinted during oocyte differentiation [28, 29], (as predicted by Lyon and Rastan [30]), the active X is always maternal in trophectoderm – the first tissue to undergo dosage compensation in the mouse embryo. Because X inactivation in the placenta occurs relatively early in mice, it is likely that the paternal X hasn’t had time to erase the inactivation imprint imposed during the early stages of spermatogenesis [31].…”
mentioning
confidence: 99%
“…Because human oocytes do not express PCR2 , which imprints the mouse oocyte, [29] and the human maternal X is not imprinted [32], and because human TSIX is ineffective, having been truncated during human evolution [32], another means of repressing the XIST locus on the future active human X is needed to protect it from being silenced. Therefore, to repress its XIST locus, recent studies suggest that the future human active X needs to interact with human chromosome 19.…”
mentioning
confidence: 99%